ANALISIS SIKAP REMAJA DALAM MENGHADAPI SINDROM PREMENSTRUASI DI SMPN 1 MAUK TANGERANG TAHUN 2019 - Yenny Aulya; Tresna Amalia Hady (Universitas Nasional, 2020)
Background: Based on World Health Organization reports, premenstrual syndrome has a higher prevalence in Asian countries compared to Western countries. Research results in Indonesia on 260 women of reproductive age, found there was 95 percent have at least one symptom of premenstrual syndrome, with moderate to severe levels of 3.9 percent. The impact of premenstrual syndrome on academic activities is a decrease in concentration of learning, and an increase in class attendance. This study aims to analyze the attitudes of adolescents on premenstrual syndrome at Junior High School 1 Mauk Tangerang in 2019. Methodology: This research is an analytic epidemiological study with a cross-sectional study design. The sample in this study were 151 people. The sampling technique uses purposive sampling. The research instrument consisted of a questionnaire about attitudes, knowledge, physical activity recall, psychology based on the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire which was a standard questionnaire, while the health education questionnaire had been tested for validity and reliability with a cronbach's alpha coefficient value of 0.66. Data were analyzed using univariate and bivariate analysis, the Chi-Square test to prove whether there was a relationship between variables. Results: The majority of adolescents had a positive attitude (50.3%) on premenstrual syndrome, high knowledge (74.2%), heavy physical activity (53.6%), psychology in the category of mild anxiety (54.3%) and high health education (53.0%). The results showed that there was a relationship between knowledge, physical activity, psychology, and health education on premenstrual syndrome. Conclusions and Recommendations: There is a relationship between knowledge, physical activity, psychology, and health education with adolescent attitudes on premenstrual syndrome. It is expected to increase knowledge about reproductive health especially about menstruation, getting used to exercising and maintaining a good lifestyle.